'Twas the Bite Before Christmas: Andy Carpenter #28 - Rosenfelt, David (New York : Minotaur Books, 2023)
" Reluctant lawyer Andy Carpenter is at the Tara Foundation's annual Christmas party. The dog rescue organization has always been his true calling, and this is one holiday tradition he can get behind because every dog that's come through the rescue--and their families--are invited to celebrate. This year's party is no exception. But before the stockings can be hung by the chimney with care, homicide detectives ruin the evening. Derek Moore, one of the foundation's best foster volunteers, is arrested for murder. Andy discovers Derek--whose real name is Bobby--is in the witness protection program after giving evidence against his former gang. The police believe Bobby murdered a member. But Bobby swears to Andy he didn't do this. He's built a new life, a new business, has two new dogs after being a double foster-failure. There isn't much Andy likes about this case, but he likes Bobby. If he's innocent, Andy wants to help. Before Andy can settle down for his long winter's nap, he has a client's name to clear, a murderer to catch, and two new dogs to look after: a golden and a Dalmatian. Andy's golden retriever, Tara, will have to adjust to not being the only golden at the house while Andy gets to the bottom of this one..."--.
new book 2023 fall.
Keywords: Carpenter, Andy -- (Fictitious character) -- Fiction; Dogs -- Fiction; Murder -- Investigation -- Fiction; Dog rescue -- Fiction; Witnesses -- Protection -- Fiction; Trials (Murder) -- Fiction; Detective and mystery fiction; Animal fiction; Novels; Christmas fiction; Detective fiction; Mystery fiction